PASUGIHAN ORANG BANJAR: STUDI IDENTIFIKASI PRILAKU DAN AMALIAH PASUGIHAN ORANG BANJAR DI KALSEL - Sani, Abdul (Faculty of Ushuluddin and Humanities, 2014)
?Pasugihan? of Banjar people (getting wealth by unusual ways) intended in this paper is three prototypes. First, the wealthy Banjar people (wealth and money). But, they get it through the ?left-way?, which maintains genies (genie mating), spirits (tuyul), stealth swine (Babi ngepet), usues Kuyang oil, and etc. Second, they take the wealth through the ?right-way?, which gets the wealth by doing Islamic ritual, such as fasting and reading sura Waqiah, doing Dhuha prayer, reading sura Alfatihah, even combining with Lailatul Qadr. This group also includes its own myth in society?s view of Banjar people. Third, the rich people who gets the wealth mythology irrational and rational. Most of this paper is the result of qualitative research methodology by relying interview techniques.